Defining the utility and market value of a real estate: A multiple criteria approach - Kaklauskas, Artūras; Zavadskas, Edmundas K.; Banaitis, Audrius; Šatkauskas, Gintautas (International Journal of Strategic Property Management, 2010)
This paper considers the application of methodology for the defining the utility and market value of a real estate. The theoretical basis of the methodology is developed. The proposed methods, the method of multiple criteria complex proportional assessment (COPRAS) and the method of defining the utility and market value of a real estate assume the dependence of priority, utility degree and value of investigated versions on a system of criteria adequately describing the alternatives and their direct proportionality to the values and weights of these criteria. The procedure of the defining the utility and market value of a real estate is discussed using an example. First published online: 18 Oct 2010